Pancreatic Enzyme Replacement Therapy and Coefficient of Fat Absorption in Children and Adolescents With Cystic Fibrosis. Issue 3 (September 2015) - Woestenenk, Janna W.; van der Ent, Cornelis K.; Houwen, Roderick H.J.
ABSTRACT: Objectives: Pancreatic enzyme replacement therapy (PERT) is the proven therapy to substantially reduce fat malabsorption in patients with cystic fibrosis (CF). Few details of the daily practice regarding PERT and the resulting coefficient of fat absorption (CFA) are known. We therefore recorded the PERT and CFA in a large cohort of pancreatic insufficient pediatric patients with CF. Methods: We retrospectively studied 1719 completed 3-day dietary food records, including the pancreatic enzyme intake registrations, and 1373 CFA assessments of 224 patients with CF, ages 0–17 years. The clinical characteristics, PERT, expressed as an intake of lipase unit (LU) per gram of fat per day and LU per kilogram per day, and the CFA were described for the group as a whole and separately for those on enteral tube feeding. Cross-sectional relationship between the CFA and the LU per gram of fat per day and LU per kilogram per day were determined for each year of age. We also addressed the effect of the interventions done in patients with CFA outcomes <85%. Results: The LU per gram of fat per day was relatively stable throughout the age groups, whereas the LU per kilogram per day fell markedly with age. The median CFA in the age group 17 varied between 86% and 91%, however, with a CFA below 85% in 325 of 1373 (24%) of the measurements. No relationship was found between PERT and CFA. The patients with persistent CFA less than 85% had significant lower z scores weight for age and weight for height ( P = 0.01) than those with CFA at least 85%. Conclusions: In this study population, no correlation between an enzyme dosage and the degree of fat malabsorption was found; however, a CFA below 85% was found in 24% of the measurements. Abstract : Supplemental Digital Content is available in the text